Button Battery Injuries in the Pediatric Aerodigestive Tract. (2nd September 2014) - Ettyreddy, Abhinav R.; Georg, Matthew W.; Mehta, Deepak; Chi, David H.; Yellon, Robert F.; Gaines, Barbara A.; Simons, Jeffrey P.
Abstract : Objectives: (1) Describe the clinical presentation, management, and complications associated with button battery impaction in the aerodigestive tract in children. (2) Evaluate the long‐term morbidity associated with button battery impaction. Methods: This study is a retrospective medical record review involving 23 consecutive patients who presented to a tertiary care childrens hospital between January 1, 2000, and July 31, 2013, with button batteries impacted in the nasal cavity (n = 7), esophagus (n = 9), and stomach (n = 7). Battery type/size, duration of impaction, presenting symptoms, treatment, and outcomes were examined. Results: Average time of battery impaction was 40.6, 30.7, and 21.0 hours in the esophagus, nasal cavity, and stomach, respectively. 3V lithium batteries accounted for 84% of battery injuries and were responsible for all cases of esophageal impaction. Most common presenting symptoms were vomiting (30.4%), fever (26%), and cough (21%). Presenting signs and symptoms did not predict severity of injury or outcomes. Average length of hospitalization was greater for esophageal impactions (43.0 days) than for nasal or stomach impactions (2.0 days; P =. 009). Batteries in the esophagus for >15 hours led to a longer postoperative hospital course and were associated with higher rates of transmural necrosis compared with those impacted for <15 hours ( P =. 04). Esophageal complications included perforation (n = 3), tracheoesophageal fistula formation (n = 2), and strictures (n = 4). Conclusions: Button battery impactions in children present with nonspecific symptoms that may account for the delay in medical care. Clinicians must consider battery impaction in the upper aerodigestive tract as a surgical emergency that may lead to significant long‐term morbidity.